Infringement of intellectual property rights: developing countries, agricultural biotechnology, and the TRIPS agreement - Giannakas, Konstantinos (International Food Policy Research Institute, 2003)
Parallel revolutions in molecular biology and intellectual property rights over plant genetic resources helped spur the emergence of agricultural biotechnologies and the introduction of genetically modified (GM) products into the food system. Intellectual property rights create economic incentives for research and development by giving innovators claim to the benefits associated with new technologies. Yet although intellectual property rights (or IPRs) purport to protect intellectual property, innovators may not always be able to fully appropriate the benefits associated with the innovation.